Interplay between 5-HT2C and 5-HT1A receptors in the dorsal periaqueductal gray in the modulation of fear-induced antinociception in mice - Baptista-de-Souza, Daniela [UNESP] (2018)
The confinement of rodents to the open arm of the elevated-plus maze provokes antinociception (OAA). As a type of defensive reaction, the OAA has been investigated through systemic and intramesencephalic (e.g., dorsal portion of the periaqueductal gray – dPAG) injections of anxiolytic-like drugs [e.g., serotonergic (5-HT) receptor agonists or antagonists]. Here we investigated the effects of (i) intra-dPAG injections of a 5HT2C receptor agonist (MK-212; 0.21 or 0.63 nmol) and antagonist (SB 242084; 0.01, 0.1 or 1.0 nmol); (ii) combined injections of SB 242084 and MK-212 into the dPAG; (iii) combined injections of SB 242084 with 8-OHDPAT (10 nmol) into the dPAG on the OAA in male Swiss mice. Nociception was assessed with the writhing test induced by acetic acid injection. Results showed that (i) intra-dPAG injection of MK-212 (0.63 nmol) increased the OAA; (ii) intra-dPAG SB 242084 (1.0 nmol) prevented the OAA; (iii) SB 242084 (0.1 nmol, a dose devoid of intrinsic effect on nociception) blocked the OAA enhancement provoked by MK-212 and enabled 8-OH-DPAT to prevent the OAA. These results suggest that OAA is mediated by 5-HT2C receptors within the dPAG. Intra-dPAG SB242084 administration provoked similar results on the effects produced by MK-212 and 8-OH-DPAT on OAA. In addition, the dPAG 5-HT1A and 5-HT2C receptors interact each other in the modulation of OAA.